How do child and adolescent mental health problems influence public sector costs? Interindividual variations in a nationally representative British sample. (29th September 2014) - Knapp, Martin; Snell, Tom; Healey, Andrew; Guglani, Sacha; Evans‐Lacko, Sara; Fernandez, Jose‐Luis; Meltzer, Howard; Ford, Tamsin
<x xml:space="preserve">Abstract</x> Background Policy and practice guidelines emphasize that responses to children and young people with poor mental health should be tailored to needs, but little is known about the impact on costs. We investigated variations in service‐related public sector costs for a nationally representative sample of children in Britain, focusing on the impact of mental health problems. Methods Analysis of service uses data and associated costs for 2461 children aged 5–15 from the British Child and Adolescent Mental Health Surveys. Multivariate statistical analyses, including two‐part models, examined factors potentially associated with interindividual differences in service use related to emotional or behavioural problems and cost. We categorized service use into primary care, specialist mental health services, frontline education, special education and social care. Results Marked interindividual variations in utilization and costs were observed. Impairment, reading attainment, child age, gender and ethnicity, maternal age, parental anxiety and depression, social class, family size and functioning were significantly associated with utilization and/or costs. Conclusions Unexplained variation in costs could indicate poor targeting, inequality and inefficiency in the way that mental health, education and social care systems respond to emotional and behavioural problems.